Localization Accuracy of Track-before-Detect Search Strategies for Distributed Sensor Networks. (6th December 2007) - Wettergren Wettergren, Thomas A. Thomas A.; Walsh Walsh, Michael J. Michael J.
Abstract : The localization accuracy of a track-before-detect search for a target moving across a distributed sensor field is examined in this paper. The localization accuracy of the search is defined in terms of the area of intersection of the spatial-temporal sensor coverage regions, as seen from the perspective of the target. The expected value and variance of this area are derived for sensors distributed randomly according to an arbitrary distribution function. These expressions provide an important design objective for use in the planning of distributed sensor fields. Several examples are provided that experimentally validate the analytical results.